IL2RA/CD25 gene polymorphisms: uneven association with multiple sclerosis (MS) and type 1 diabetes (T1D). - Alcina, Antonio; Fedetz, María; Ndagire, Dorothy; Fernández Fernández, Óscar; Leyva-Fernández, Laura; Guerrero, Miguel; Abad-Grau, María del Mar; Arnal, Carmen; Delgado, Concepción; Lucas, Miguel; Izquierdo, Guillermo; Matesanz, Fuencisla (Public Library of Science, 2009)
Background:IL-2 receptor (IL2R) alpha is the specific component of the high affinity IL2R system involved in the immune response and in the control of autoimmunity. Methods and Results: Here we perform a replication and fine mapping of the IL2RA gene region analyzing 3 SNPs previously associated with multiple sclerosis (MS) and 5 SNPs associated with type 1 diabetes (T1D) in a collection of 798 MS patients and 927 matched Caucasian controls from the south of Spain. We observed association with MS in 6 of 8 SNPs. The rs1570538, at the 39- UTR extreme of the gene, previously reported to have a weak association with MS, is replicated here (P = 0.032). The most associated T1D SNP (rs41295061) was not associated with MS in the present study. However, the rs35285258, belonging to another independent group of SNPs associated with T1D, showed the maximal association in this study but different risk allele. We replicated the association of only one (rs2104286) of the two IL2RA SNPs identified in the recently performed genome-wide association study of MS. Conclusions:These findings confirm and extend the association of this gene with MS and reveal a genetic heterogeneity of the associated polymorphisms and risk alleles between MS and T1D suggesting different immunopathological roles of IL2RA in these two diseases.
Versión publicada del artículo
Keywords: Diabetes; Esclerosis múltiple; IL2IL2RA/CD25; Polymorphisms; Multiple sclerosis; Type I diabetes